Expression of the cellular prion protein by mast cells in white-tailed deer carotid body, cervical lymph nodes and ganglia - Anthony E. Kincaid; Nathaniel D. Denkers; Erin E. McNulty; Caitlyn N. Kraft; Jason C. Bartz; Candace K. Mathiason (Prion)
Chronic wasting disease (CWD) is a transmissible and fatal prion disease that affects cervids. While both oral and nasal routes of exposure to prions cause disease, the spatial and temporal details of how prions enter the central nervous system (CNS) are unknown. Carotid bodies (CBs) are structures that are exposed to blood-borne prions and are densely innervated by nerves that are directly connected to brainstem nuclei, known to be early sites of prion neuroinvasion. All CBs examined contained mast cells expressing the prion protein which is consistent with these cells playing a role in neuroinvasion following prionemia.